Alternative model for the fine porous structure in hydrated tricalcium silicate - Vollet, Dimas R. [UNESP]; Craievich, Aldo F. (Emerald, 1988)
Hydrated tricalcium silicate has been studied by small angle X-ray scattering (SAXS). The experimental SAXS results have been compared with those expected from a lamellar model and from the Debye, Anderson and Brumberger (DAB) model. The theoretical SAXS intensity for the DAB structural model agrees closely with the experimental results. In addition the DAB model provides a good explanation of the different values of specific surface area determined by SAXS, adsorption and proton NMR methods. © 1988, Thomas Telford Ltd. All rights reserved.